Coping strategies of physically handicapped university students in Iloilo City. - Robles, Baby Rose Gargantiel (1992.)
The researcher noted the presence of physically handicapped college students in a university, despite of their physical limitations. With this observation, the researcher aims to determine the different coping strategies a typical students employ, in trying to cope with the curricular requirements and social demands of college life. This study considered three intervening variables, gender, type of impairment and nature of impairment. The researcher used porpusive sampling for the reliability of items test or pre-test, availing the twenty-two physically handicapped college students enrolled in the seven colleges in Iloilo City. The respondents include those who are visually impaired such as the blind and partially sighted and students with orthopedic impairments such as poliomyelitis/paralysis crippled, amputations, cerebral palsy and with speech defects. For the final test, purposively sampled physically handicapped college students enrolled in the five universities in Iloilo City, with the same impairments were taken as respondents. Coping strategies were assessed using the 100-item checklist containing specific coping strategies. The specific coping strategies were categorized into three modes, namely: instrumental, intrapsychic and information seeking strategies, which was patterned after the Ways of Coping Checklist by Folkman and Lazarus (1985). Each of the item was pretested using the Empirical Criterion Keying. Seventy-one reliable items appeared, thirty for instrumental strategies, twenty-one for intrapsychic strategies and twenty for information seeking strategies. Finally, it was determined that among the respondents, there were varying results in the modes of coping strategies that they employ. There were differences in the coping strategies employed by the respondents when separated according to type of impairment and nature of impairment. It was alsodetermined by the study that the coping strategies employed by male and female respondents were similar. Hence, gender is not a determinant of their employment of specific coping strategies. On the other hand, their type and nature of impairments are determinants of their employment of specific coping strategies. The conclusion was obtain through the Index of Coping Strategies.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Handicapped students -- Iloilo City